Implementasi Kepemimpinan Transformasional dalam Meningkatkan Kinerja Organisasi - Nina Puspita; Novita Maharani; Fifin Wildanah (CV. ITTC INDONESIA, 2025)
Leadership plays a crucial role in enhancing organizational effectiveness, especially in times of change and when striving to boost employee performance. One widely adopted approach is transformational leadership, where leaders serve as a source of inspiration and motivation, encouraging employees to perform optimally through a clear vision and innovative strategies (Robbins & Judge, 2017). This study explores the benefits of transformational leadership in improving organizational performance, using a literature review method that examines various academic sources on the topic. The findings indicate that this leadership style enhances employee motivation, loyalty, and productivity. According to Bass & Riggio (2016), transformational leadership consists of four key components: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These elements contribute to a more creative and collaborative work environment, ultimately supporting organizational effectiveness. Furthermore, the study highlights that organizations implementing transformational leadership tend to be more adaptable to change and achieve higher levels of productivity (Yukl, 2020). Leaders who adopt this style not only set the organizational direction but also guide and support employees in achieving strategic goals. Thus, transformational leadership can be an effective strategy for enhancing competitiveness and ensuring organizational sustainability.